2009
DOI: 10.4049/jimmunol.0900552
|View full text |Cite
|
Sign up to set email alerts
|

An Activating and Inhibitory Signal from an Inhibitory Receptor LMIR3/CLM-1: LMIR3 Augments Lipopolysaccharide Response through Association with FcRγ in Mast Cells

Abstract: Leukocyte mono-Ig-like receptor 3 (LMIR3) is an inhibitory receptor mainly expressed in myeloid cells. Coengagement of FcεRI and LMIR3 impaired cytokine production in bone marrow-derived mast cells (BMMCs) induced by FcεRI crosslinking alone. Mouse LMIR3 possesses five cytoplasmic tyrosine residues (Y241, Y276, Y289, Y303, Y325), among which Y241 and Y289 (Y241/289) or Y325 fit the consensus sequence of ITIM or immunotyrosine-based switch motif (ITSM), respectively. The inhibitory effect was abolished by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 45 publications
2
89
1
Order By: Relevance
“…Two putative ITIMs encompassing Y205 and Y249 have been identified, and a substitution (tyrosine into phenylalanine) analysis revealed that these were required for the CD300F-mediated inhibitory effects (8). However, the action mechanism of CD300F still requires more detailed analysis because cross-linking of mouse CD300F, in contrast to the previously mentioned results, augmented LPS response through its association with FcRg in mast cells (7) and induced apoptotic cell death in human acute myeloid leukemia and myeloid cells (9,10).…”
mentioning
confidence: 42%
See 1 more Smart Citation
“…Two putative ITIMs encompassing Y205 and Y249 have been identified, and a substitution (tyrosine into phenylalanine) analysis revealed that these were required for the CD300F-mediated inhibitory effects (8). However, the action mechanism of CD300F still requires more detailed analysis because cross-linking of mouse CD300F, in contrast to the previously mentioned results, augmented LPS response through its association with FcRg in mast cells (7) and induced apoptotic cell death in human acute myeloid leukemia and myeloid cells (9,10).…”
mentioning
confidence: 42%
“…In experimental autoimmune encephalomyelitis, CD300F expression was detected on inflammatory myeloid cells present in demyelinated areas and the absence of CD300F increased production of the proinflammatory mediators and aggravated the clinical symptoms (5). In addition, cross-linking of CD300F has been shown to inhibit the inflammatory activation of macrophages induced by the stimulation of BAFF, a member of the TNF superfamily (6) and activation of mast cells induced by FcεR stimulation (1,7). Furthermore, overexpression CD300F in RAW264.7 cells inhibited osteoclastogenesis induced by the RANKL, another member of TNF superfamily (3).…”
mentioning
confidence: 99%
“…Consequently, mouse CD300f has been shown to serve as either an activating or an inhibitory receptor (17,18,(45)(46)(47)(48). Our previous work showed that the CD300f cytoplasmic tail initiates either positive or negative signals for phagocytosis of ACs upon recognition of PS (17).…”
Section: Animals Cd300fmentioning
confidence: 99%
“…The 3 0 UTR was cloned to downstream of the Renilla luciferase stop codon in pGL4.74 vector (Promega, Madison, WI, USA). To generate the mutant 3 0 UTR of the mouse Trp53inp1, two-step PCR mutagenesis was performed [24][25][26] using the WT-3 0 UTR as a template. The Rluc-2 Â 125b site vector contained two copies of a sequence designed to be perfectly complementary to the miR125b downstream of the Renilla luciferase stop codon.…”
Section: Luciferase Assaymentioning
confidence: 99%